Novel approaches to analysis of 3-chloropropane-1,2-diol esters in vegetable oils - Moravcová, Eliška; Vaclavik, Lukáš; Lacina, Ondřej; Hrbek, Vojtěch; Riddellová, Kateřina; Hajšlová, Jana (Analytical and bioanalytical chemistry, 2012)
A sensitive and accurate method utilizing ultrahigh performance liquid chromatography (U-HPLC) coupled to high resolution mass spectrometry based on orbitrap technology (orbitrapMS) for the analysis of nine 3-chloropropane-1,2-diol (3-MCPD) diesters in vegetable oils was developed. To remove the interfering triacylglycerols that induce strong matrix effects, a clean-up step on silica gel column was used. The quantitative analysis was performed with the use of deuterium-labeled internal standards. The lowest calibration levels estimated for the respective analytes ranged from 2 to 5 μg kg(-1). Good recovery values (89-120%) and repeatability (RSD 5-9%) was obtained at spiking levels of 2 and 10 mg kg(-1). As an alternative, a novel ambient desorption ionization technique, direct analysis in real time (DART), hyphenated with orbitrapMS, was employed for no separation, high-throughput, semi-quantitative screening of 3-MCPD diesters in samples obtained by chromatographic fractionation. Additionally, the levels of 3-MCPD diesters measured in reallife vegetable oil samples (palm oil, sunflower oil, rapeseed oil) using both methods are reported. Relatively good agreement of the data generated by U-HPLC-orbitrapMS and DART-orbitrapMS were observed. With regard to a low ionization yield achieved for 3-MCPD monoesters, the methods presented in this paper were not yet applicable for the analysis of these contaminants at the naturally occurring levels.
Keywords: hmotnostní spektrometrie; Chromatography, High Pressure Liquid; Mass Spectrometry; Esters; Glycerol; estery; glycerol; Plant Oils; oleje rostlin; vysokoúčinná kapalinová chromatografie